2011
DOI: 10.1016/j.theriogenology.2011.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Long-term fertility control in female cats with GonaCon™, a GnRH immunocontraceptive

Abstract: The uncontrolled reproduction of free-roaming feral cats contributes to overpopulation and associated concerns regarding their welfare and impact on public health and the environment. Nonsurgical fertility control that could be administered to feral cats in the field would be a powerful tool for cat population control. The objective was to test the efficacy and duration of activity of a single-dose GnRH immunocontraceptive vaccine (GonaCon™) on the fertility of adult female laboratory cats. Vaccinated cats (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
118
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(127 citation statements)
references
References 22 publications
2
118
2
2
Order By: Relevance
“…Gonacon TM is very effective in inducing contraception after a single injection in many different mammals although the effects are generally more consistent in females than males [2,3,24,38]. In our trials in male Balb/c mice, a single injection of Gonacon TM induced anti-GnRH immune responses and gonadal atrophy in some, but not all of the mice.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Gonacon TM is very effective in inducing contraception after a single injection in many different mammals although the effects are generally more consistent in females than males [2,3,24,38]. In our trials in male Balb/c mice, a single injection of Gonacon TM induced anti-GnRH immune responses and gonadal atrophy in some, but not all of the mice.…”
Section: Discussionmentioning
confidence: 61%
“…In our trials in male Balb/c mice, a single injection of Gonacon TM induced anti-GnRH immune responses and gonadal atrophy in some, but not all of the mice. This variable response could indicate that the administered dose was sub-optimal or that male Balb/c mice are less sensitive to this vaccine compared to other mammals in which it has been tested [38]. In our studies, animals injected with ISCOMs formulations showed an enlarged spleen, an effect which could be due to the presence of a saponin component; some saponin adjuvants are known to possess an angiogenic effect and the spleen enlargement may thus be caused by increased blood supply [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37] Pre-and post-pubertal rams and boars accumulate androgen derivatives namely androstenone and skatole in their adipose tissues, which gives an unpleasant odor to meat. Therefore, castration of male pigs is routinely performed in order to prevent the occurrence of the boar taint.…”
Section: Veterinary Applications Of Gnrh-based Contraceptive Vaccinementioning
confidence: 99%
“…Since resources are insufficient to manage unwanted cats with current surgical sterilisation techniques, which require considerable investments of time, money and manpower, future successful management will likely rely on methods of permanent non-surgical sterilisation, such as immunocontraceptive vaccines (Goericke-Pesch, 2010;Levy et al, 2011;Munks, 2012). Contraceptive vaccines have been used effectively in deer and seals, and non-surgical contraception is considered to be a realistic future goal (Kass, 2005;Levy et al, 2011;Munks, 2012).…”
Section: Cats Without An Ownermentioning
confidence: 99%
“…Contraceptive vaccines have been used effectively in deer and seals, and non-surgical contraception is considered to be a realistic future goal (Kass, 2005;Levy et al, 2011;Munks, 2012).…”
Section: Cats Without An Ownermentioning
confidence: 99%